Rhetorical argumentation in biblical texts - Eriksson, Anders; Olbricht, Thomas H.; Ubelacker, Walter (Emory studies in early Christianity, 2002)
In the latest volume in the Emory Studies in Early Christianity series, the contributors seek a better understanding of how various biblical authors present their arguments, support their claims, and attempt to persuade their readers. A century ago the rhetorical analysis of texts focused on the study of rhetorical figures in texts (elocutio). In the mid-twentieth century, scholars such as James Muilenburg, Hans Dieter Betz, and Wilhelm Wuellner introduced biblical scholars to the illustrious tradition of rhetorical study. These scholars tended to focus on the arrangement of the texts themselves (dispositio). During the last ten years, however, interpreters have increasingly studied the rhetorical argumentation in texts. The authors in this volume examine rhetorical argumentation in the Hebrew Bible, the Gospels, the Pauline letters, and the Book of Revelation, offering striking new readings of these materials.